Impact Investing from an European Perspective – Do Good and Earn Money? - Reuthlinger, Eva; Sinha, Tanja (Copernican Journal of Finance & Accounting, 2025)
Impact Investing provides a promising way to fund sustainable development while balancing financial, social, and environmental goals. This study compares the performance of Impact, Conventional, and ESG Portfolios in the European stock market over more than 10 years, using Markowitz Optimization and Naive Diversification. The findings show that Impact Portfolios yield the highest returns, without sacrificing financial performance when integrating sustainability criteria that go beyond the classical ESG investing.